Prevalence and Management of Periodontal Diseases in Gezira Province (Central Sudan) - Abdelrahman Yousif, Mugahid; Ibrahim Miskeen, Elhadi (مجلة الجزيرة للعلوم الصحية; مجلد 4 عدد 2 (2008), 2008)
Objectives : This study aimed to assess the status of present periodontal diseases in Gezira Province. The facilities investigated included those in urban and rural areas including Wad Medani Dental hospital, Wad Medani Military Hospital, El Gadaiea Health Centre and Maringan Health Centre. Methodology : The study tools were direct pre-coded questionnaires, and a checklist. The procedure involved dental clinical examinations of patients to estimate periodontal diseases assessed by measuring calculus, gingival bleeding and periodontal pockets (PI index). The study sample was randomly selected to comprise 10% of patients attending Wad Medani Dental and Military Dental Hospitals during a week time period (6 days). All patients attended El Gadaiea and Marinjan Health Centres (n = 201) and sampled patients at rural health institutions during the same period were recruited (n = 448). Results: Thirty study sites in the rural areas were chosen from five study councils including Alhosh, Wad Alnaeem, Alhag Abdalla, Almadina Arab and Hantoub. They comprise 418 towns, villages and camps, of the only 118 had health services, including only four dental units. This was the reason that most of rural populations seek oral health services for periodontal diseases and dental caries in Wad Medani health institutions. The result showed that the prevalence of gingivitis and periodontal diseases were more prominent in the rural areas, while the management of them were meager in both the urban and rural areas. Conclusion: From the results of the present study could be concluded that there was a high prevalence of periodontal diseases due to poor provision of dental services in both quantity and quality at Gezira Province.